The effects of peripheral hormone responses to exercise on adult hippocampal neurogenesis - Kraemer, Robert R.; Kraemer, Bradley R. (Frontiers in Endocrinology, 2023)
Over the last decade, a considerable amount of new data have revealed the beneficial effects of exercise on hippocampal neurogenesis and the maintenance or improvement of cognitive function. Investigations with animal models, as well as human studies, have yielded novel understanding of the mechanisms through which endocrine signaling can stimulate neurogenesis, as well as the effects of exercise on acute and/or chronic levels of these circulating hormones. Considering the effects of aging on the decline of specific endocrine factors that affect brain health, insights in this area of research are particularly important. In this review, we discuss how different forms of exercise influence the peripheral production of specific endocrine factors, with particular emphasis on brain-derived neurotrophic factor, growth hormone, insulin-like growth factor-1, ghrelin, estrogen, testosterone, irisin, vascular endothelial growth factor, erythropoietin, and cortisol. We also describe mechanisms through which these endocrine responses to exercise induce cellular changes that increase hippocampal neurogenesis and improve cognitive function.